1981
DOI: 10.1002/hep.1840010512
|View full text |Cite
|
Sign up to set email alerts
|

Iepatic vitamin D 25-hydroxylase: Inhibition by bile duct ligation or bile salts

Abstract: Bone disease and low serum levels of 25-hydroxyvitamin D are prevalent in cholestatic syndromes such as primary biliary cirrhosis and biliary atresia. Defective hydroxylation, along with malabsorption of vitamin D, could be a factor in 25-hydroxyvitamin D depletion. To assess hepatic hydroxylation during experimental cholestasis, we studied vitamin D 25-hydroxylase activity in liver homogenates of rats after 7, 14, and 21 days of bile duct ligation. We have also studied the effects of bile acids on this enzyme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0

Year Published

1985
1985
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 31 publications
1
9
0
Order By: Relevance
“…Impaired bone formation in chronic liver disease may be responsible for failure of osteomalacia to become apparent as mineralisation defects develop only in newly laid down osteoid. Earlier studies suggested that a decrease in 25-hydroxylase activity was responsible for the osteodystrophy found in bile duct ligated rats 30 This could not be confirmed in CCl 4 treated rats. 31 Vitamin D metabolism has not been studied in portacaval shunting.…”
Section: Discussionmentioning
confidence: 88%
“…Impaired bone formation in chronic liver disease may be responsible for failure of osteomalacia to become apparent as mineralisation defects develop only in newly laid down osteoid. Earlier studies suggested that a decrease in 25-hydroxylase activity was responsible for the osteodystrophy found in bile duct ligated rats 30 This could not be confirmed in CCl 4 treated rats. 31 Vitamin D metabolism has not been studied in portacaval shunting.…”
Section: Discussionmentioning
confidence: 88%
“…The activation of hepatic stellate cells involves the increased cellular proliferation, increased synthesis of extracellular matrix proteins, and the expression of the activation marker a-SMA (Miyazaki et al 1993). Previous investigations have demonstrated that BDL cause progressive bile stasis, focal necrosis, bile ductular proliferations, and periportal inflammation in rats (Bolt et al 1981). Extracellular matrices in liver fibrosis are known to be produced by myofibroblasts that are transformed from fatstoring cells.…”
Section: Discussionmentioning
confidence: 98%
“…The activation of hepatic stellate cells involves the increased cellular proliferation, increased synthesis of extracellular matrix proteins, and the expression of the activation marker α-SMA [49]. Previous investigations have demonstrated that BDL cause progressive bile stasis, focal necrosis, bile ductular proliferations, and periportal inflammation in rats [50]. Extracellular matrices in liver fibrosis are known to be produced by myofibroblasts that are transformed from fatstoring cells.…”
Section: Discussionmentioning
confidence: 98%